Examining the type and frequency of incidents attended by UK paramedics. (2nd September 2019) - Henderson, Tristan; Endacott, Ruth; Marsden, Jonathan; Black, Sarah
Abstract : Various factors have widened the variety of incidents that UK paramedics, practising in a non-specialist role, may be required to attend. This study set out to identify the type and frequency of incidents attended by paramedics, as well as establishing whether geographical location and time of year bear any influence. The study involved a quantitative retrospective review of paramedic-completed patient clinical records, across two locations and the span of 1 year. Results demonstrated the infrequent exposure of paramedics to serious illness/trauma, as well as limited associations of significance in relation to location and time of year. The infrequent nature of certain incidents raises potential issues of skill decay for paramedics; closely aligned to this is their ongoing education, and how learning is best balanced between the infrequent, serious presentations, and those that are frequent but less serious.